IMPROVEMENT OF THE METHODOLOGY OF TEACHING BIOLOGY IN HIGHER EDUCATIONAL INSTITUTIONS BASED ON ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Turekeeva, Alfiya Zhienbekovna (SCIENCE and SOCIETY, 2026)
This article extensively covers the theoretical, didactic, and practical aspects of improving the process of teaching biology in higher educational institutions based on artificial intelligence technologies. The possibilities of individualizing education using digital intellectual tools, forming an adaptive learning environment, organizing virtual laboratory classes, automatic knowledge analysis, and supporting pedagogical decision-making were analyzed. A step-by-step methodological model of integrated artificial intelligence for biology education is proposed, and its effectiveness is substantiated based on the results of experimental work and statistical analysis.